ASSESSMENT OF THE ECOLOGICAL STATE OF THE PAPAN RESERVOIR BY BASIC HYDROCHEMICAL INDICATORS DURING SEASONAL CHANGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article provides information about changes in the hydrochemical regime of the Papan reservoir depending on the season and the chemical composition of the water. The purpose of the study: to evaluate the hydrochemical and hydrological condition of the Papan reservoir in relation to the season of the year. Tasks of the study: 1. Collection of data on the hydrochemical regime of the Papan reservoir. 2. Average result for each indicator in the period from 2010 to 2020, analysis of the hydrochemical regime of the Papan reservoir for some indicators.
Keywords: reservoir, research methods, hydrobiological regime, hydrochemical regime